The micropaleontological analysis data (short sediment cores from the Arcona, Bornholm, and Gdansk Basins of the Baltic Sea) - Ponomarenko, Ekaterina; Pugacheva, Tatiana; Kuleshova, Liubov (PANGAEA, 2024)
The data for the paleoenvironmental study was obtained on the basis of complex analysis of short sediment cores retrieved in the Arcona, Bornholm, and Gdansk Basins of the Baltic Sea. The cores were collected using a short gravity sediment corer (Niemistö type). The upper layers (0-5 cm) of sediment cores were stained with the 80% ethanol solution of rose Bengal following the protocol (Schönfeld et al., 2012, doi:10.1016/j.marmicro.2012.06.001) and were used only for the microfossil analysis. The rests of the cores (below the 5 cm) were continuously sampled with the 1 cm step and were used for the loss on ignition (LOI), microfossil, X-ray fluorescence (XRF), and grain-size analyzes. For the micropaleontological analysis the samples were sieved through >63 μm mesh using tap water. Benthic foraminifera shells and inner organic linings were counted in a wet state following the (Brodniewicz, 1965; Binczewska et al., 2018, doi:10.1111/bor.12267).
Keywords: Arcona Basin; Benthic foraminifera; Bornholm Basin; Gdansk Basin; inner organic lining; short sediment core